2020
DOI: 10.1177/1403494820929496
|View full text |Cite
|
Sign up to set email alerts
|

The effect of household crowding and composition on health in an Inuit cohort in Greenland

Abstract: Aims: This study aims to investigate the association between household crowding and household composition and self-rated health and mental health (GHQ scale) among the Inuit in Greenland. Poor housing conditions are a concern in Greenland, especially in the villages, where socioeconomic standards in general are lower. Methods: A cohort of 1282 adults participated in two population-based surveys in Greenland, the Inuit Health in Transition survey 2005–2010 (baseline) and The Health Survey in Greenland 2014 (fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The increase in the sense of home was also a significant contributor to psychological distress improvements. In contrast, longitudinal analyses from other studies conducted in Inuit regions have shown inconclusive results regarding the association between crowding and mental health outcomes [ 47 , 48 ].…”
Section: Literature Reviewmentioning
confidence: 94%
“…The increase in the sense of home was also a significant contributor to psychological distress improvements. In contrast, longitudinal analyses from other studies conducted in Inuit regions have shown inconclusive results regarding the association between crowding and mental health outcomes [ 47 , 48 ].…”
Section: Literature Reviewmentioning
confidence: 94%
“…The average floor area per person in the EU is 42.6 m 2 per person 31 ; hence the variable was dichotomized as < 43 m 2 or ≥ 43 m 2 per person. Household crowding 32 , 33 was adapted from the Eurostat criteria 34 with alterations due to data constraints. A minimal number of rooms for a given household was calculated as follows: (i) one room for the household; (ii) one room per couple in the household; (iii) one room for each adult single person; (iv) ½ room for each child.…”
Section: Methodsmentioning
confidence: 99%
“…Household crowding was categorized as reference (minimal or minimal + 1), crowded (< minimal), and under-occupied (> minimal + 1). Based on previous literature 33 , household composition 35 was categorized as households with children, adult-only households, and single-person households. Dwelling type was categorized as apartment versus house.…”
Section: Methodsmentioning
confidence: 99%
“…From 2014 the funding for the interviews was provided by the Department of Health in Greenland whereas funding for the clinical part of the surveys was provided from a number of public and private research foundations. Results were primarily reported to the Department of Health in Greenland and later in peer-reviewed scientific journals [ 1 , 2 ]. The data are administered by the National Institute of Public Health at the University of Southern Denmark on mandate by the government of Greenland.…”
Section: Previous Population Health Surveysmentioning
confidence: 99%